2010
DOI: 10.1051/0004-6361/201014355
|View full text |Cite
|
Sign up to set email alerts
|

Centaurus A: morphology and kinematics of the atomic hydrogen

Abstract: We present new ATCA 21-cm line observations of the neutral hydrogen in the nearby radio galaxy Centaurus A. We image in detail (with a resolution down to 7 , ∼100 pc) the distribution of H i along the dust lane. Our data have better velocity resolution and better sensitivity than previous observations. The H i extends for a total of ∼15 kpc. The data, combined with a titled-ring model of the disk, allow to conclude that the kinematics of the H i is that of a regularly rotating, highly warped structure down to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 60 publications
4
91
0
1
Order By: Relevance
“…Even invoking an extreme time-delay between these events (longer than in other studied cases, see Emonts et al 2006), the fact that more than one stage of activity is seen cannot be unambiguously linked to clear events in the process of building of the gas disk. This is reminiscent of what was already found in the case of Centaurus A (Struve et al 2010b). Therefore, despite the large reservoir of H I in the disk, the actual fuel of the AGN may have a different origin.…”
Section: Recurrent Activity and Supply Of Gassupporting
confidence: 84%
“…Even invoking an extreme time-delay between these events (longer than in other studied cases, see Emonts et al 2006), the fact that more than one stage of activity is seen cannot be unambiguously linked to clear events in the process of building of the gas disk. This is reminiscent of what was already found in the case of Centaurus A (Struve et al 2010b). Therefore, despite the large reservoir of H I in the disk, the actual fuel of the AGN may have a different origin.…”
Section: Recurrent Activity and Supply Of Gassupporting
confidence: 84%
“…2.3.1). Various authors (Stickel et al 2004;Struve et al 2010;Auld et al 2012) have reported the existence of cold clouds along the jet axis but offer no direct evidence for jet-cloud interaction. We choose to also neglect the contribution from cold gas to the total entrainment.…”
Section: Constraints On Energy Density and Magnetic Fieldsmentioning
confidence: 99%
“…Though galaxy transformations can happen in lower density environments (Cappellari et al 2011), they occur more often in dense groups and clusters. Substantial H i debris are typically detected near massive, often early-type galaxies (Schneider 1989;Ryder et al 2001;Bekki et al 2005a,b;Chung et al 2009;English et al 2010;Struve et al 2010). In particular, we highlight the ATLAS-3D H i results for a large sample of nearby early-type galaxies, which show a 40% H i detection rate for the non-cluster targets…”
Section: Introductionmentioning
confidence: 99%